Earthen blocks with natural fibres - A review. (2021) - Jesudass, A.; Gayathri, V.; Geethan, R.; Gobirajan, M.; Venkatesh, M.
Abstract: Earthen materials have been used for thousands of years for its easy availability and cost effectiveness. In recent times, earthen materials are gaining its momentum as the entire world understood the need of sustainability in all walks of life. It is mainly used for its sustainability and low environmental impact. To keep up with conventional building materials, fibres are incorporated into the earthen materials to enhance the performance in both strength and durability aspects. This study presents a comprehensive review of studies involving earthen blocks with natural fibres to enhance the performance of the block. Studies done with earthen blocks reinforced with ten natural fibres (viz. Date palm, jute, coconut, Hemp, Sisal, Banana, Chicken, Sugarcane bagasse, Corn, Wool fibres) were reviewed with a brief summary of physical, chemical and mechanical properties. Literature search was conducted using Google Scholar and web of science libraries. Banana fibre, date palm fibre, sugarcane, and jute fibres reinforced blocks are considerably performing better in strength, durability aspects. The adhesion property between fibre and soil are achieved by chemical treatments. Lack of treatment to fibre prior to usage in blocks was observed. Aspect ratio and tensile test on fibres were missing in many studies. Future studies can be conducted on the effect of treatment to fibres and block performance characteristics.